Screening of chinese medicinal herbs for the inhibition of Brucella melitensis - Khoo, Wen Wen; Bejo, Siti Khairani (2010)
The antimicrobial activities of extracts from Chinese herbs commonly available in the local Malaysian Chinese medicine halls against three field isolates and one reference strain of Brucella melitensis were evaluated. A total of ten herb extracts were obtained via ethanol extraction. Antibacterial screenings were done using disc diffusion method. Herb extracts with inhibitory zones of 10 mm or more in diameter were further subjected to the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) determination. Of the 10 herbs, which were Lunicera japonica, Flos Lonicera, Coptis chinensis, Adrographis paniculata, Isatis indigotica, Radix paeoniae rubra, Polygonum orientale, Galla chinensis, Semen plantaginis, Fructus forsythia and Cortex phellodendrim, four were found to possess inhibitory effect against Brucella melitensis strains. The herbs are Coptis chinensis, Radix paeoniae rubra, Galla chinensis, and Cortex phellodendrin. The MIC ranged from 3.75 to 30 mg/mL. It was suggested that these four herbs are potential alternatives for the treatment or prevention of brucellosis caused by Brucella melitensis.